The Effect of Exercising Employee Stock Options on Investment in Taiwanese Firms - Ting, Yu-Chieh (2015)
The purpose of this study is to examine whether the proceeds from stock option exercises can influence on investment in Taiwanese listed firms. Since the proportion of high-tech firms account for the most in Taiwan, the study expects that the sensitivity of R&D expenses to the cash inflows received from exercising stock options is significantly positive, In addition, high percentage of firms in Taiwan are multinational enterprises which tend to invest in oversees where the costs of running businesses are lower. Therefore, the study predicts the effect of exercising stock options on FDI is also statistically positive. The data is collected from Taiwanese Economic Journal database, including 2,218 firm-year stock option observations from 402 listed firms between 2003 and 2009. Other financial data are merged with the stock option data by hand collecting. The final sample used in the analysis comes to 2,814 firm-year observations. The panel data analysis is used in the study. Furthermore, in order to investigate whether the influence of the proceeds from stock option exercises on investment can vary cross different financing constraints, the regression discontinuity approach is also employed. The study expects that the effect of the stock option proceeds on investment is greater for firms facing high cost financing. The results indicate the influence of the stock option proceeds on R&D is larger than the influence on FDI. The coefficient estimates explain that $0.948 of each dollar of the proceeds from stock option exercises is assigned to R&D expenditures and 0.498 of each dollar of the stock option exercise proceeds is allocated to FDI spending. However, the correlation between the proceeds from stock option exercises and investment is not significant when firms face costly external financing.